Antifibrotic effects of gallic acid on hepatic stellate cells: In vitro and in vivo mechanistic study - Naglaa M. El-Lakkany; Walaa H. El-Maadawy; Sayed H. Seif el-Din; Samira Saleh; Marwa M. Safar; Shahira M. Ezzat; Salwa H. Mohamed; Sanaa S. Botros; Zeinab Demerdash; Olfat A. Hammam (Journal of Traditional and Complementary Medicine, 2019)
Few studies reported the antifibrotic effects of gallic acid (GA) despite its known hepatoprotective and antioxidant activities. Accordingly, this study investigated the antifibrotic effects of GA through clarifying its mechanisms on hepatic stellate cells' (HSCs) activation, proliferation and/or apoptosis. In vitro effects of GA on HSC-T6 activation/proliferation, morphology and safety on hepatocytes were assessed. In vivo, hepatic fibrosis was induced via chronic thioacetamide (TAA)-intoxication. TAA-intoxicated rats were treated with silyamrin or GA. At end of experiment, liver functions, hepatic MDA, GSH, PDGF-BB, TGF-β1, TIMP-1 and hydroxyproline were determined. Histological analysis and Sirius red staining of hepatic sections, expressions of alpha-smooth muscle actin (α-SMA), proliferating cellular nuclear antigen (PCNA) and caspase-3 were examined. In vitro, GA resulted in a concentration and time-dependent inhibition in HSCs activation, proliferation (IC50= 45 and 19 μg/mL at 24 and 48 h respectively); restored the quiescent morphology of some activated HSCs plus its safety on hepatocytes. In vivo, GA reduced ALT, AST, MDA, PDGF-BB levels, collagen deposition and fibrosis score (S1 vs S4); increased caspase-3 expression and restored GSH stores, TGF-β1 level, α-SMA and PCNA expressions. In conclusion, GA counteracted the progression of hepatic fibrosis through reduction of HSCs proliferation/activation mutually with their apoptosis induction. Keywords: Gallic acid, Hepatic stellate cells, Hepatocytes, Proliferation/activation, Apoptosis